Development of a Novel Whey Date Beverage Fermented with Kefir Grains Using Response Surface Methodology - Sana M’hir; Kais Rtibi; Asma Mejri; Manel Ziadi; Hajer Aloui; Moktar Hamdi; Lamia Ayed (Journal of Chemistry)
The aim of this study was to develop a novel kefir beverage using date syrup, whey permeate, and whey. The levels of the kefir grain inoculum (2–5% w/v), fruit syrup (10–50% w/v), and whey permeate (0–5% w/v) on pH, total phenolic content, antioxidant activity, lactic acid bacteria and yeast counts, and overall acceptability were investigated using central composite design. The use of response surface methodology allowed us to obtain a formulation with acceptable organoleptic properties and high antioxidant activities. The obtained beverages had total phenolic content, % DPPH scavenging activity, and overall acceptability ranging from 24 to 74 mg GAE/mL, from 74.80 to 91.37 mg GAE/mL, and from 3.50 to 6 mg GAE/mL (based on a 1 to 9 preference scale), respectively. Date syrup of 36.76% (w/v), whey permeates of 2.99%, and kefir grains inoculum size of 2.08% were the optimized process conditions achieved.